Phase formation of identity homosexuality: Study descriptive at the lesbian in Bandung - Handi, Ginar Zsalsabila; Achdiani, Yani; Abdullah, Mirna Nur Alia (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
In the phenomenon of lesbians, there is a process of self-meaning of lesbian individuals, in other words, how lesbian individuals are in the stage of forming their homosexual identity. Lesbian self-meaning cannot be formed and realized as a person's sexual orientation but through stages that are influenced by psychosocial and biological factors that can shape one's identity. The purpose of this study is to find out how the stages of homosexual identity formation follow Cass's Theory which is a model for analyzing the formation of homosexual identities, including lesbians. The method used is a descriptive study with a qualitative approach to describe phenomena related to the self-meaning process of lesbians. The results obtained based on the research are the stages of lesbian identity formation, types of lesbian self-meaning, and barriers in the process of lesbian self-meaning. Recommendations from researchers are that understanding and research related to the phenomenon of lesbian self-meaning should continue to be expanded and developed in order to provide insight to the public in accepting the diversity of sexual orientations and reducing stigma and acts of discrimination.